Is Drinking Alcohol Really Linked to Cardiovascular Health? Evidence from the Kardiovize 2030 Project - Maugeri, Andrea; Hlinomaz, Ota; Agodi, Antonella; Barchitta, Martina; Kunzova, Sarka; Bauerova, Hana; Sochor, Ondrej; Medina-Inojosa, Jose R; Lopez-Jimenez, Francisco; Vinciguerra, Manlio; Stokin, Gorazd Bernard; González-Rivas, Juan Pablo (Nutrients, 2020)
Existing data have described benefits and drawbacks of alcohol consumption on cardiovascular diseases (CVD), but no research has evaluated its association with the cardiovascular health (CVH) score proposed by the American Heart Association. Here, we conducted a cross-sectional analysis on the Kardiovize cohort (Brno, Czech Republic), to investigate the relationship between alcohol consumption and CVH. We included 1773 subjects (aged 25-64 years; 44.2% men) with no history of CVD. We compared CVD risk factors, CVH metrics (i.e., BMI, healthy diet, physical activity level, smoking status, blood pressure, fasting glucose, and total cholesterol) and CVH score between and within several drinking categories. We found that the relationship between drinking habits and CVH was related to the amount of alcohol consumed, drinking patterns, and beverage choices. Heavy drinkers were more likely to smoke tobacco, and to report diastolic blood pressure, fasting glucose, triglycerides, and low-density lipoprotein (LDL)-cholesterol at higher level than non-drinkers. Among drinkers, however, people who exclusively drank wine exhibited better CVH than those who exclusively drank beer. Although our findings supported the hypothesis that drinking alcohol was related to the CVH in general, further prospective research is needed to understand whether the assessment of CVH should incorporate information on alcohol consumption.
Keywords: drinking habits; Male; Tobacco Smoking; Risk Factors; Wine; krevní glukóza; Adult; nutritional epidemiology; dospělí; mužské pohlaví; public health; kardiovaskulární nemoci; lidé; krevní tlak; ženské pohlaví; Humans; cardiovascular disease; cardiometabolic health; ethanol; Ethanol; pivo; rizikové faktory; Blood Pressure; pití alkoholu; Alcohol Drinking; Beer; Cardiovascular Diseases; Female; Blood Glucose; lidé středního věku; víno; kouření tabáku; Middle Aged